2004
DOI: 10.1186/1471-2474-5-15
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of facet joint pain in chronic spinal pain of cervical, thoracic, and lumbar regions

Abstract: Background: Facet joints are a clinically important source of chronic cervical, thoracic, and lumbar spine pain. The purpose of this study was to systematically evaluate the prevalence of facet joint pain by spinal region in patients with chronic spine pain referred to an interventional pain management practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
339
1
14

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 391 publications
(364 citation statements)
references
References 58 publications
5
339
1
14
Order By: Relevance
“…The proportion of people affected by low back pain for whom facet joint pain is a contributing factor is unclear. In an interventional pain management practice study the prevalence of chronic back pain being caused by facet joints was reported to be 31 % [8].…”
mentioning
confidence: 99%
“…The proportion of people affected by low back pain for whom facet joint pain is a contributing factor is unclear. In an interventional pain management practice study the prevalence of chronic back pain being caused by facet joints was reported to be 31 % [8].…”
mentioning
confidence: 99%
“…Disk degeneration leads to abnormal weight transfer and motion in the spine and results in facet joint arthritis [6]. It has been reported that as many as 89% -95% individuals of 65 and older have varying degrees of Facet Joint Arthritis (FJAO) and the L4-5 and L5-S1 are the most commonly affected joints [1,3,4,6].…”
Section: Introductionmentioning
confidence: 99%
“…As any typical synovial joint, facet joints have two articular surfaces formed by inferior articular process (IAP) of the upper vertebra and the superior articular process (SAP) of the lower vertebra [2]. Facet joints are potential source of pain in low back pain (LBP) and its prevalence increases with age [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Chronic zygapophyseal joint arthropathy is a known cause of neck pain [1,9,10] the common causes being degenerative and post-traumatic. The phenomenon of degenerative facet joint osteoarthritis is considered to be a secondary effect of disc degeneration (cervical spondylosis).…”
Section: Introductionmentioning
confidence: 99%
“…The most commonly involved levels in cervical spondylosis are C5-C6 and C6-C7 [2,8]. One proposed method of treating facet joint pathology secondary to degenerative and post-traumatic cervical disorders non-surgically is facet joint infiltration [1,5,7,[9][10][11]. Radiologists under computer tomography (CT) guidance or physiatrists, pain management specialists and surgeons using fluoroscopy (C-arm) usually perform facet joint injections.…”
Section: Introductionmentioning
confidence: 99%